Seaports and Seaport Terminals - Bird, J. H. (London : Hutchinson, 1971)
A seaport is a functional meeting place not only of many trades but also of many professions. In essence, the main aim of this book has been to draw forth from seaport study such useful generalizations as can be made, using real life cases as illustrative examples.
Includes index
Includes bibliographies.
ne 06/03/2018
Loan
Keywords: Harbors